2019
DOI: 10.2147/ppa.s201088
|View full text |Cite
|
Sign up to set email alerts
|

<p>Satisfaction analysis of patients with single implant treatments based on a questionnaire survey</p>

Abstract: Background: The factors influencing satisfaction of the patients with implant treatments are still unclear. This study aims to evaluate the patients’ satisfaction and to identify influencing factors, which will improve the medical quality of oral implantology. Materials and methods: Patients who lost single teeth and received implant treatments were enrolled in Nanjing Stomatological Hospital between February 2016 and March 2018. A questionnaire survey was performed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…To deal with this dilemma, various methods, such as guided bone regeneration, transposition of the inferior alveolar nerve, and the use of tilted implants and short implants, have been made available for clinicians to employ . However, the complications, higher cost, and increasing surgical time of the former three techniques have raised new concerns …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To deal with this dilemma, various methods, such as guided bone regeneration, transposition of the inferior alveolar nerve, and the use of tilted implants and short implants, have been made available for clinicians to employ . However, the complications, higher cost, and increasing surgical time of the former three techniques have raised new concerns …”
Section: Introductionmentioning
confidence: 99%
“…3 However, the complications, higher cost, and increasing surgical time of the former three techniques have raised new concerns. 4 Short implants were designed in response to the proper time and conditions, although there were doubts regarding the crown-toimplant ratio (C/I ratio). However, a recent research suggests that the C/I ratio was negatively correlated to the short implant loss if not exceeded 1.7.…”
mentioning
confidence: 99%
“…The clinical performance of NDIs has been broadly reported in previous studies. 2,20 This retrospective study analyzed NDIs placed in the upper anterior region followed up for 4 years by experienced and professional dentists from Nanjing Stomatological Hospital. We collected multifaceted information during the follow-up period to evaluate the risk factors of NDIs and found that the surface characteristics were significantly associated with NDI failures.…”
Section: Discussionmentioning
confidence: 99%
“…41 Moreover, for younger patients (≤65 years old) and those with shorter period of edentulism, it is more difficult to get positive answers regarding OHRQoL, masticatory function and satisfaction. [42][43][44] Most included patients aged ranging from 49 to 86 years and different periods of edentulism were recorded, which may lead to the difference between the studies. Additionally, the majority of studies were carried out in university-affiliated hospitals, except for one study in private clinics, which is a significant confounding factor regarding 'satisfaction'.…”
Section: Confounding Factors Of Promsmentioning
confidence: 99%